PREFERENSI KONSUMEN TERHADAP DAGING AYAM BROILER DI ERA NEW NORMAL: Consumer Preferences For Broiler Chicken In The New Normal Era - Danang Priyambodo; Intani Dewi; Gilang Ayuningtyas (IPB University, 2020)
The purpose of this study was to determine consumer attitudes towards the attributes of fresh chicken meat and frozen chicken meat and to analyze the factors that influence consumers in purchasing decisions for fresh chicken meat and frozen chicken meat in the city of Bogor in the new normal era. This research was conducted in October-Desember 2020. Data obtained from 250 respondents who usually buy broiler chicken meat and is divided into several areas namely modern market, traditional market, and chicken selling places around the city of Bogor. The sample of respondents in the study was chosen purposively and the data collection technique used a survey method through direct interviews based on the questions contained in the questionnaire. The data were analyzed with descriptive analysis and Fishbein models. The result of the study concluded that: 1) Broiler meat consumers were mostly female of adult age and married, has the last education of senior high school, works as a housewife and has an income of less than IDR 1.000.000. 2) All broiler meat consumers carry out all stages of purchasing decisions. 3) The factors that influence the purchase of broiler chicken meat with the highest average score (4.42) are based on health factors. 4) Based on the Fishbein model, the highest average value (Ao) is found in fresh meat products, which means that respondents in the city of Bogor in the new normal era prefer fresh chicken meat products to frozen chicken meat products.